2010
DOI: 10.2139/ssrn.1444009
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Management and Corporate Investment During a Financial Crisis

Abstract: We thank CFO Magazine for helping us conduct the surveys, though we note that our analysis and conclusions do not necessarily reflect those of CFO. We thank Benjamin Ee and Hyunseob Kim for excellent research assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
128
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 23 publications
(37 reference statements)
14
128
1
3
Order By: Relevance
“…Both results are in agreement with evidence provided by Akbar et al (2013). This finding proves the rationale for debt frontloading documented by Ivashina and Scharfstein (2010) and Campello et al (2011), providing evidence of heavy credit line drawdowns at the onset of the financial crisis due to concerns among firms about the ability of banks to provide liquidity, which might lead to temporary credit being taken beyond the optimal amount for investment. The access to debt before the economic and credit contraction might improve the company's outlook for better utilization of its capacities and enable it to restructure during the period of hardship.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Both results are in agreement with evidence provided by Akbar et al (2013). This finding proves the rationale for debt frontloading documented by Ivashina and Scharfstein (2010) and Campello et al (2011), providing evidence of heavy credit line drawdowns at the onset of the financial crisis due to concerns among firms about the ability of banks to provide liquidity, which might lead to temporary credit being taken beyond the optimal amount for investment. The access to debt before the economic and credit contraction might improve the company's outlook for better utilization of its capacities and enable it to restructure during the period of hardship.…”
Section: Resultssupporting
confidence: 88%
“…More recently, Buca and Vermeulen (2012) looked at a sample of European firms and found that profitable investment opportunities have been foregone by bank-dependent firms, which faced credit constraints during the 2009 financial crisis. Ivashina and Scharfstein (2010) and Campello et al (2011) document heavy credit line drawdowns at the onset of the financial crisis due to firms' concern about the ability of banks to provide liquidity. Schoder (2013) adds to this discussion by studying the relative importance of supply and demand conditions on investment over the cycle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding builds upon previous literature, which shows that the relaxation of bank branching laws in the 1970s and 1980s led to beneficial product market effects, such as higher rates of new firm incorporations as well as an increase in the number of firms in operation (e.g., Black and Strahan, 2002;Cetorelli and Strahan, 2006). Third, our study is related to the literature on the role of bank credit lines in corporate liquidity management (e.g., Houston and James, 2001;Sufi, 2009;Campello et al, 2011) and the literature on the causes and consequences of contagion in financial and product markets (e.g., Lang and Stulz, 1992;Calomiris et al, 1995;Kohler et al, 2000;Nilsen, 2002;Choi and Kim, 2005;Hertzel et al, 2008;Cohen and Frazzini, 2008;Duchin et al, 2010;Hertzel and Officer, 2012;Houston et al, 2012;Boissay and Gropp, 2013). Finally, a contemporaneous paper by Garcia-Appendini and Montoriol-Garriga (2013) uses cash holdings as a liquidity measure and shows that more liquid suppliers offered higher trade credit to less liquid customers during the 2007-2008 crisis.…”
supporting
confidence: 83%
“…Another survey-based study on corporate liquidity management choices is Campello et al (2009). The authors survey 794 CFOs employed by public and private firms from 31 countries regarding their firms' liquidity choices before and during the 2007 credit crisis.…”
Section: Firms' Choice Between Cash and Bank Lines Of Creditmentioning
confidence: 99%